2007
DOI: 10.1007/s12149-007-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of the gastrointestinal tract: FDG-PET imaging

Abstract: We assess the usefulness of F-18-fluoro-deoxyglucose (FDG) positron emission tomography (PET) in the evaluation of gastrointestinal metastases. Four cases (five lesions) in which metastases from three lung cancers and one malignant fibrous histiocytoma (MFH) of the femur were found in the gastrointestinal tract were reviewed (men/women 3 : 1, age 63-78 years, mean 72 years). The five lesions were duodenal, jejunal metastasis, and two stomach metastases from lung carcinoma, and rectal metastasis from MFH of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
4
1
1
Order By: Relevance
“…Hayakawa et al reported the identification of four secondary lesions in three patients (two metastases to stomach, one to the duodenum, and one to the jejunum) of the 308 patients who underwent PET. 20 In the present study, the rate of detecting metastasis of the gastrointestinal tract from lung cancer was two (0.2%) of 1071 patients; this incidence was lower than that found at autopsy. Of the two cases, only one patient (with perforation of the small intestine due to metastasis from lung adenocarcinoma) had clinical symptoms.…”
Section: Discussioncontrasting
confidence: 52%
“…Hayakawa et al reported the identification of four secondary lesions in three patients (two metastases to stomach, one to the duodenum, and one to the jejunum) of the 308 patients who underwent PET. 20 In the present study, the rate of detecting metastasis of the gastrointestinal tract from lung cancer was two (0.2%) of 1071 patients; this incidence was lower than that found at autopsy. Of the two cases, only one patient (with perforation of the small intestine due to metastasis from lung adenocarcinoma) had clinical symptoms.…”
Section: Discussioncontrasting
confidence: 52%
“…However, it is sometimes diYcult to diagnose peritoneal metastasis using only conventional techniques. For a more exact diagnosis of carcinomatosis, other methods, such as PET scans, staging laparoscopy, or peritoneal lavage cytology have been introduced (Hayasaka et al 2007;Nakagawa et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…12 This modality has detected asymptomatic GI lesions from a primary lung cancer as described in literature, 25 and is advocated by Hayasaka et al, finding four GI metastases from primary lung tumors in 308 patients undergoing a whole-body PET scan. 26 However, the role of this modality is not clear due to the relatively few cases of GI metastasis from primary lung cancer and the general lack of such clinical data. 12 Furthermore, the relative 34,41 or small/large bowel metastasis 39 at autopsy Antler et al 34 (423 patients) Yoshimoto et al 41 insensitivity of this test is apparent through an estimated rate of 25% in the detection of extra-thoracic lesions of lung cancer.…”
Section: Diagnosismentioning
confidence: 99%